Subject case alternation in negated existential, locative, and possessive clauses in Latvian - Kalnača, Andra; Lokmane, Ilze (Kalbotyra, 2018)
[full article and abstract in English]The goal of this article is to analyse the alternation between the genitive and nominative cases in Latvian. As the alternation between genitive and nominative cases is possible in all clauses in which the verb būt ‘to be’ is used as an independent verb, this article examines existential, locative, and also possessive clauses, while also demonstrating that distinguishing these clause types is problematic for Latvian utilising the criteria given in the linguistic literature. Clauses containing the negative form of būt ‘to be’, i.e. nebūt, form the foundation of those selected for this study, as only in these sentences the genitive/nominative alternation can be seen for the subject in Latvian.There are only fragmentary descriptions of existential clauses as a unique semantic type, primarily in connection with the function of the verb būt ‘to be’ and the problems associated with distinguishing its independent and auxiliary meanings. Word order in existential, locative, and possessive clauses has, until now, been examined in connection with typical clause expanders – adverbial modifiers and the dative of possession as well as the information structure of the clause. At the same time, case choice for objects in negative existential clauses has traditionally been one of the most studied themes regarding language standardisation. In order to determine which factors affect the choice of either the genitive or nominative case, a corpus study was done analysing 979 examples: 882 with a genitive subject and 97 with a nominative subject. It was found that a connection exists between the definiteness of the subject, word order, and case choice; however, this manifests only as a tendency rather than as a strict rule.
Keywords: existential clauses; possessive clauses; locative clauses; genitive; nominative; subject